The practicality of popular scientific book of aquatic plant on mangrove habitat in the form of flipbook to college students’ critical thinking skill - Antung Fitriani; Dharmono Dharmono; Badruzsaufari Badruzsaufari (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
In the 21st century, critical thinking skills are one of the essential abilities that greatly influence the academic and professional success of students. One of the learning resources that can train students' critical thinking skills is a learning resource that contains local potential. One of the learning resources that can be developed based on local potential is popular scientific books that are in accordance with the characteristics of critical thinking skills which are packaged in flipbook form to make it easier for students to access during the current pandemic. Popular scientific books (BIP) with the characteristics of critical thinking skills that were developed to overcome the problems of students' critical thinking skills. This study aims to describe the practicality of popular scientific books on aquatic plants in mangrove habitats in the form of flipbooks on students' critical thinking skills. The practicality data of BIP in the form of a flipbook was obtained from a one to one test to determine student readability using a readability questionnaire, small group test and field test to determine the practicality of expectations and actual practicality using a student response questionnaire and the results of observing the implementation of BIP use using an implementation questionnaire. This study uses a development research design with an EDR model through formative evaluation from Tessmer. Respondents are students who have passed the Plant Botany course program. The data analysis used descriptive categorization technique.Abstrak Di abad 21, keterampilan berpikir kritis merupakan salah satu kemampuan essensial yang sangat berpengaruh terhadap kesuksesan akademik dan professional mahasiswa. Salah satu sumber belajar yang dapat melatihkan keterampilan berpikir kritis mahasiswa adalah sumber belajar yang memuat potensi lokal. Sumber belajar yang dapat dikembangkan dengan berbasis potensi lokal salah satunya adalah buku ilmiah populer yang sesuai dengan karakteristik keterampilan berpikir kritis yang dikemas dalam bentuk flipbook untuk memudahkan mahasiswa dalam mengakses pada masa pendemi saat ini. Buku ilmiah populer (BIP) dengan karakteristik keterampilan berpikir kritis yang dikembangkan untuk mengatasi permasalahan keterampilan berpikir kritis mahasiswa. Penelitian ini bertujuan untuk mendeskripsikan kepraktisan buku ilmiah populer tumbuhan air pada habitat mangrove berbentuk flipbook terhadap keterampilan berpikir kritis mahasiswa. Data kepraktisan BIP berbentuk flipbook didapatkan dari uji one to one untuk mengetahui keterbacaan mahasiswa menggunakan angket keterbacaan, uji small group dan uji field test untuk mengetahui kepraktisan harapan dan kepraktisan aktual dengan menggunakan angket respon mahasiswa dan hasil observasi keterlaksanaan penggunaan BIP menggunakan angket keterlaksanaan. Penelitian ini menggunakan desain penelitian pengembangan dengan model EDR melalui evaluasi formatif dari Tessmer. Responden merupakan mahasiswa yang sudah lulus program mata kuliah Botani Tumbuhan. Analisis data menggunakan teknik deskriptif kategorisasi.